ANALYSIS OF THE PROSPECT AND OBSTACLES OF ISLAMIC EDUCATION IN THE AEC ERA - Malik, Adam; Maulana, Wildhan (Proceeding of International Conference on Islamic Education (ICIED); Vol 5 No 1 (2020): Proceeding of International Conference on Islamic Education (ICIED), 2021)
It is known that globalization is a mechanism for national economic integration between nations into a global economic system. Besides globalization also includes cultural systems characterized by the tendency of all regions in the world both physically and geographically to have similarities in cultural, social, political, educational, and economic patterns. In the context of social life, the mechanism of globalization has given birth to a culture of egalitarianism which has triggered the liberalization of the political order and the internationalization of culture. Furthermore, globalization has been propagated as an era of a bright future, in which economic growth can take place so fast that it is hoped that it will bring prosperity to the global community. Based on the previous explanation globalization has also had a significant impact on increasing obstacles to Islamic education because in the era of the AEC (ASEAN Economic Community) each educator is required to always excel in the aspects of qualifications, competence, productivity, and welfare so that they are not easily marginalized in level competition regional and global. To answer these problems efforts to develop the teaching profession needs to be increased by reviewing the fundamental aspects of each change incompetence.